MODERN METHODS OF FOOD INTOLERANCE TESTING - M. Yu. Rosensteyn; A. Z. Rosensteyn; S. E. Kondakov; N. A. Cherevko (Бюллетень сибирской медицины)
Аn analytical review of modern methods of food intolerance diagnostics based on interpretation of markers used in the various tests is рresented. It is shown that tests based on observation of the reaction of specific antibodies of the immune system to food antigens tested, are the most accurate, reliable and representative for the diagnosis of food intolerance.